Perencanaan Teknis Pembangunan Jalan di Dusun I, Desa Baumata Timur, Kecamatan Taebenu, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Bela, Krisantos Ria; Pedo, Krisantus Satrio Wibowo; Bone, Richardus Korsini Eno; Mali, Adrianus Yuventus (CV. Gio Architect, 2024)
The construction of road infrastructure in Dusun I, Baumata Timur Village, Taebenu Sub-district, Kupang Regency, is an urgent need to improve accessibility and the welfare of the local community. This activity is carried out by students and lecturers from the Faculty of Engineering, Widya Mandira Catholic University of Kupang through the Community Service Program (KKN). The technical planning process for the road construction includes field observations to evaluate the physical condition of the road, discussions with village authorities to identify needs and gain support, and the preparation of a construction proposal that includes a budget plan (RAB) and technical specifications. Observations revealed critical road conditions with significant damage hindering community mobility. The documents produced include survey documentation, planning drawings, and a budget plan with a total cost of THREE BILLION FOUR HUNDRED TEN MILLION FIVE HUNDRED TWENTY THOUSAND RUPIAH, encompassing general works, drainage, earthworks and geosynthetics, granular pavement, asphalt pavement, and structures. It is hoped that this road construction will facilitate the flow of goods and services and support local economic development, thereby improving the welfare of the community in Dusun I, Baumata Timur Village.